Impact Assessment of Driver Distraction by Cellphone on Start-up Lost-time and Average Saturation Headway at Signalized Intersections Based on Vehicle Position in the Queue - Alshabibi, Nawaf (Periodica Polytechnica Transportation Engineering, 2021)
Cellphone usage has a significant impact on signalized intersections' capacity and level of service. This study investigated the impact of cellphone usage on signalized intersection capacity and level of service in Dammam Metropolitan Area, Saudi Arabia. The data included 183 useful cycles and 2407 start-up lost time and average saturation headway values at cycles with cellphone usage and cycles without cellphone usage at 24 signalized intersections. The main hypothesis of the study is that cellphone usage increases the start-up lost time at signalized intersection capacity. The secondary hypothesis is that cellphone usage increases the average saturation headway at signalized intersections. Normal distribution and z-test were conducted to assess whether there is a significant increase in average saturation headway and start-up lost time. The study found a significant increase in start-up lost time of about 0.7 seconds but found no significant increase in average saturation headway due to cellphone usage. Also, start-up lost time increases as vehicles of cellphone users get closer to the stop line of the signalized intersections. Thus, cellphone usage decreases the progression of 13 vehicles per hour due to a reduction in effective green time, increases total delay, and deteriorates the level of service. The study can assist transportation and traffic officials to optimize signal operation to mitigate the impact of cellphone usage and improve urban transportation.